TXD568 : Applied textile / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course focuses on creating creative ideas from selected textiles and other material for textile based product items for fashion accessories, soft furnishings, interiors decorations, stationaries and crafts. Students are required to do an indepth research on various textile products, textile techniques, technical specifications and creative embellishments to create textile products which are creative, innovative, contemporary, functional and also practical. In achieving these goals, students must be aggressive in developing concepts and ideas, and develop a keen study in identifying textile products, materials and current trends. Presentation of creative technical illustrations using variety of contemporary methods are equally important next to the knowledge in the production process of the textile product itself.